Characterization of extremal KMS states on groupoid C*-algebras - Lima, Rafael Pereira (2019)
In this master\'s thesis we study a theorem due to Neshveyev which describes all KMS states on the groupoid C*-algebra for a locally compact Hausdorff second countable étale groupoid. Then we study a result due to Thomsen which characterizes the extremal KMS states on this C*-algebra for a Renault-Deaconu groupoid.